Effects of palm bunch potash, trona and their modified cashew gum-corn starch composite on the physicochemical properties of furosemide - Ebere I. Okoye; Austinline C. Ekweogu; Ugochukwu E. Oruna (GarVal Editorial Ltda., 2017)
Context: In Nigeria, traditional cuisines are prepared using either palm bunch ash (PBA) or trona to impart emulsification, tenderizing and flavouring attributes to oils, proteins and polysaccharides in delicacies. Hypothesis is that they may improve the solubility and dissolution profiles of poorly soluble and permeable drug as furosemide. Aims: To investigate the effects of palm bunch potash (PBP), trona and modified cashew gum-corn starch composite on the physicochemical properties of furosemide. Methods: To generate PBP and purified trona, PBA or powdered trona was dispersed in water, filtered, centrifuged and supernatant evaporated to dryness. Cashew gum (CG) and cashew gum-corn starch composite (EC) were modified by mixing with PBP or trona at 5:1 and 10:1, wetted with water, stored in amber vials for 72 h. Furosemide was granulated with modified excipients at 1:1 ratio and characterized: FTIR, DSC, solubility and dissolution studies. Results: Yield of PBP: 9.38 ± 1.24%, trona: 24.18 ± 0.93%. FTIR spectra of furosemide/granules were similar and retained key functional groups present in furosemide. Their DSC thermograms revealed complete amorphization of furosemide in granules. Mixing of PBP or trona and excipients at 5:1 ratio significantly (p<0.05) improved furosemide's solubility in comparison to 10:1. Excipient-trona was a significantly (p<0.05) better enhancer of furosemide's solubility than excipient-PBP. Modified excipients significantly (p<0.05) improved furosemide's dissolution profile, while unmodified cashew gum reduced it by 50%. Dissolution profile improvement by modified excipients ranked in the order: CG-Trona > CG-PBP > EC-Trona > EC-PBP. Conclusions: Trona, PBP, modified excipients positively altered the physicopharmaceutical properties of furosemide.